Rapamycin and inulin for third-dose vaccine response stimulation (RIVASTIM): Inulin – study protocol for a pilot, multicentre, randomised, double-blinded, controlled trial of dietary inulin to improve SARS-CoV-2 vaccine response in kidney transplant recipients. Issue 12 (1st December 2022) - Singer, Julian; Tunbridge, Matthew; Perkins, Griffith B; Salehi, Tania; Ying, Tracey; Wu, Huiling; Coates, P Toby; Chadban, Steven J
Abstract : Introduction: Kidney transplant recipients (KTRs) are at an increased risk of hospitalisation and death from COVID-19. Vaccination against SARS-CoV-2 is our primary risk mitigation strategy, yet vaccine effectiveness in KTRs is suboptimal. Strategies to enhance vaccine efficacy are therefore required. Current evidence supports the role of the gut microbiota in shaping the immune response to vaccination. Gut dysbiosis is common in KTRs and is a potential contributor to impaired COVID-19 vaccine responses. We hypothesise that dietary fibre supplementation will attenuate gut dysbiosis and promote vaccine responsiveness in KTRs. Methods and analysis: Rapamycin and inulin for third-dose vaccine response stimulation-inulin is a multicentre, randomised, prospective, double-blinded, placebo-controlled pilot trial examining the effect of dietary inulin supplementation prior to a third dose of COVID-19 vaccine in KTRs who have failed to develop protective immunity following a 2-dose COVID-19 vaccine schedule. Participants will be randomised 1:1 to inulin (active) or maltodextrin (placebo control), administered as 20 g/day of powdered supplement dissolved in water, for 4 weeks prior to and following vaccination. The primary outcome is the proportion of participants in each trial arm that achieve in vitro neutralisation of live SARS-CoV-2 virus at 4 weeks following a third dose of COVID-19 vaccine. Secondary outcomes include the safety and tolerability of dietary inulin, the diversity and differential abundance of gut microbiota, and vaccine-specific immune cell populations and responses. Ethics and dissemination: Ethics approval was obtained from the Central Adelaide Local Health Network (CALHN) Human Research Ethics Committee (HREC) (approval number: 2021/HRE00354) and the Sydney Local Health District (SHLD) HREC (approval numbers: X21-0411 and 2021/STE04280). Results of this trial will be published following peer-review and presented at scientific meetings and congresses. Trial registration number: ACTRN12621001465842.